ESTADO DE DEPRESSÃO RELACIONADO À AUTONOMIA FUNCIONAL DE IDOSOS PRATICANTES DE EXERCICIOS FÍSICOS (Fiep Bulletin - online, 2024)
Introduction: Evidence indicates that physical ctivity is one of the low-cost means of solving physiological and psychological problems. In this way, Objective: To relate the chronic effects of resistance exercises on functional autonomy, reducing the risk of falls, as well as associating it the impacto n the state of depresion in the elderly.  Methods: This article consists of a secondary review of the literature, the information gathering involved the Google Scholar and Scielo platforms, with works published in the last ten years. The discriptors used were “depression in the elderly”, “functional capacity and the elderly” and “depression and functional autonomy”. The inclusion criteria were to present the mentioned Keywords associated with the boolean term “and”, as exclusion was given to studies that were not related to the proposed objective. Results: Four studies were selected, which allowed us to confirm that the regular practice of Physical activity generates positive effects on Physical and emotional aspects. Conclusion: This should strengthen the need for public policies that promote Physical exercise programs for this population.